Stabilization of a rydberg-laser system for measurements of atom-surface interactions. - Chua, Chern Fei. (2011)
In this final year project, we build a Rydberg laser system for an experiment which will be used to measure the interaction between the Rydberg atoms and a surface. The laser system consists of two home-built 780nm external cavity diode lasers (ECDL) and a commercial 480nm frequency doubler laser. The 480nm laser is used to excite atoms to Rydberg states. The laser has to be stabilized to a Rydberg state, by utilizing the electromagnetically induced transparency (EIT). The 480nm will then coupled to the experiment setup, to excite atoms to Rydberg states by two photon transition, together with the 780nm laser. In order to check if the atoms are in the Rydberg state, another 780nm ECDL is built for imaging. The whole frequency stabilization setup for this Rydberg laser system uses home-built electronics such as temperature controller, lock-in amplifiers and PI controllers. Radio frequency (RF) electronics are also used for driving acoustic optic modulator (AOM), which are used to modulate the laser frequency externally. Finally, the lasers will be delivered to the experiment by single mode fibers. This laser system will be used to study the Rydberg atom-surface interaction in the experiment. The experimental setup and the basic theory of EIT, Rydberg atoms and atom surface interaction are discussed in this report.